THE IMPACT OF BRAND IMAGE, PRICE, AND SERVICE QUALITY ON PURCHASE DECISIONS AND CUSTOMER SATISFACTION: IMPLICATIONS FOR CUSTOMER LOYALTY IN THE HORISON HOTEL GROUP – WEST JAVA - gustaf leonandri, dino; Wala Erpurini, Wala Erpurini (Jurnal Riset Bisnis dan Manajemen, 2025)
This study examines the influence of brand image, pricing, and service quality on purchasing decisions and customer satisfaction, as well as their combined impact on customer loyalty at Hotel Horison Group in West Java. Motivated by a decline in sales and occupancy rates from 2022 to 2024, the research aimed to identify key factors affecting customer loyalty. Using a descriptive-explanatory approach, data were collected through interviews, questionnaires, and direct observation, with proportionate random sampling. The study, conducted in 2014, utilized Structural Equation Modeling (SEM) for data analysis. Findings reveal that brand image, price, and service quality each have a significant positive effect on purchasing decisions and customer satisfaction. These factors, in turn, contribute meaningfully to customer loyalty. The results underscore the importance of improving brand image, offering competitive pricing, and enhancing service quality as strategic efforts to build and sustain customer loyalty at Hotel Horison Group.